(untitled) (IUBAT Review, 2024)
This study reports the design of an optimized heat exchanger capable of efficiently extracting and transferring waste heat from flue gas to air. An experimental setup was constructed to recover waste heat from the exhaust steam of a boiler, using this heat to warm compressed air. Thermocouples recorded the temperatures at the inlet and outlet of both the hot and cold fluids. A MATLAB code is developed to compare the experimental results. According to our code, the cold fluid outlet temperature ranged from 71.5°C to 76°C, while the experimental setup showed temperatures ranging from 66°C to 71.5°C at air mass flow rates of 0.1564, 0.1346, and 0.1794 kg/s. The deviation may arise from the inaccuracies of the flow rate and the temperature measurement devices as well as the constraints in correlations which calculate heat transfer coefficient and friction factor in pressure drop. Future work may focus on minimizing the deviations and propose an improved design of heat exchanger. IUBAT Review—A Multidisciplinary Academic Journal, 7(1): 124-141